Development Of Android-Based Learning Media On The Basics Of Algorithm And Programming For Class X Students Of Rantauprapat Regional Vocational School - Aldimas Adianang; Masrijal Masrijal; Irmayanti Irmayanti (Eduvest - Journal of Universal Studies, 2024)
This research uses a quantitative approach to test the hypotheses proposed in the research in the form of numbers and analysis using statistics, with the aim of the research being to determine the development of Android-based learning media products on the basics of Algorithms and Programming, as well as the feasibility of Android-based learning media. on the basics of Algorithms and Programming for class X students of Rantauprapat Regional Government Vocational School. The results of this research are Android-based learning media on the basics of Algorithms and Programming for class Meanwhile, the results of testing by material experts obtained an overall average of 88.6% in the "Very Eligible" category. The results of the feasibility test by students were 82.47% which was included in the "Very Eligible" category. So overall it can be concluded that the learning media developed is very suitable for use.